Prevalence and predictors of involuntary psychiatric hospital admissions in Ontario, Canada: a population-based linked administrative database study. Issue 2 (22nd February 2018) - Lebenbaum, Michael; Chiu, Maria; Vigod, Simone; Kurdyak, Paul
Abstract : Background: Involuntary admissions to psychiatric hospitals are common; however, research examining the trends in prevalence over time and predictors is limited. Aims: To examine trends in prevalence and risk factors for involuntary admissions in Ontario, Canada. Method: We conducted an analysis of all mental health bed admissions from 2009 to 2013 and assessed the association between patient sociodemographics, service utilisation, pathway to care and severity characteristics for involuntary admissions using a modified Poisson regression. Results: We found a high and increasing prevalence of involuntary admissions (70.7% in 2009, 77.1% in 2013, 74.1% overall). Individuals with police contact in the prior week (risk ratio (RR) = 1.20) and immigrants both experienced greater likelihood of being involuntarily admitted, regardless of control for other characteristics (RR = 1.07) (both P < 0.0001). Conclusions: We identified numerous modifiable and non-modifiable risk factors for involuntary admissions. The prevalence of involuntary admissions was high, linearly increasing over time. Declaration of interest: The authors have completed the ICMJE Form for Disclosure of Potential Conflicts of Interest and none were reported. This study was conducted using funding entirely from public sources. P.K. has received operational support via an Ontario Ministry of Health and Long-Term Care (MOHLTC) Health Services Research Fund Capacity Award to support this project. The Institute for Clinical Evaluative Sciences (ICES) is funded by the Ontario MOHLTC. The study results and conclusions are those of the authors, and should not be attributed to any of the funding agencies or sponsoring agencies. No endorsement by ICES or the Ontario MOHLTC is intended or should be inferred. All decisions regarding study design, publication, and data analysis were made independent of the funding agencies.